2013
DOI: 10.1002/ece3.561
|View full text |Cite
|
Sign up to set email alerts
|

Population differentiation of the African cyprinid Barbus neumayeri across dissolved oxygen regimes

Abstract: Population level response to hypoxia has become an issue of global significance because of increased frequency and intensity of hypoxic events worldwide, and the potential for global warming to exacerbate hypoxic stress. In this study, we sequenced two nuclear intronic regions and a single mitochondrial region across seven populations of the African cyprinid, Barbus neumayeri from two river drainages in Uganda: the Rwembaita Swamp-Njuguta River System and the Dura River. We then examined two indices of populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 46 publications
(94 reference statements)
0
7
0
Order By: Relevance
“…Pairwise Φ ST s and Jost's D of COI sequences were calculated to investigate interpopulation genetic differentiation (Jost, ; Portnoy et al ., ; Harniman et al ., ). Populations on artificial structures were genetically different from populations on the northern natural rocky shore (NNRS), with few exceptions (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…Pairwise Φ ST s and Jost's D of COI sequences were calculated to investigate interpopulation genetic differentiation (Jost, ; Portnoy et al ., ; Harniman et al ., ). Populations on artificial structures were genetically different from populations on the northern natural rocky shore (NNRS), with few exceptions (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…Small‐bodied Enteromius and Clarias spp. are rhithronic species with preferences for cover and limnophilic features (Fugère, Mehner, et al, 2018; Harniman et al, 2013; Muñoz‐Mas et al, 2019). The longitudinal distribution of fishes in the Sondu‐Miriu River is also influenced by the Odino Waterfalls, which prevent the upstream migration of fishes.…”
Section: Discussionmentioning
confidence: 99%
“…Agricultural streams were deforested over 50 years ago, which should provide ample time for adaptation given that evolution in physiological traits can occur over only a few generations in some fishes (Barrett et al, 2011;Handelsman et al, 2013). Gene flow could prevent adaptive TA B L E 2 Results of ANCOVA or ANOVA models testing effects of body size, stream land use and watershed on field growth rates divergence, yet our mark recapture study indicated no apparent dispersal among populations (see also Harniman et al, 2013). The absence of population differences could also be due to low heritability of RMR (but see Burton, Killen, Armstrong, & Metcalfe, 2011), "cryptic adaptive evolution" caused by opposing effects of adaptation and phenotypic plasticity (Conover & Schultz, 1995;Grether, 2005) or, perhaps most likely, no selection on RMR because metabolic costs of warming do not influence fitness, as our results for natural growth rates suggest.…”
Section: Discussionmentioning
confidence: 88%
“…In each watershed, the farm and forest fish populations are separated by a hypoxic papyrus swamp with a dissolved oxygen concentration generally <1 mg O 2 L −1 (watershed 1: Chapman, Chapman, Brazeau, McLaughlin, & Jordan, ; watershed 2: L. Chapman, unpublished data; Figure S1b). Genetic and mark–recapture studies have indicated that stream‐adapted populations of E. neumayeri very rarely disperse through papyrus swamps (Chapman et al., ; Harniman, Merritt, Chapman, Lesbarreres, & Martinez, ), suggesting low gene flow between farm and forest populations within each watershed. Molecular studies have also established that populations from watersheds 1 and 2 are genetically distinct (Harniman et al., ), confirming that each forest–farm population pair constitutes an independent replicate to study thermal adaptation to deforested (warmer) conditions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation